2011
DOI: 10.1002/ppap.201000162
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Nanoclays by Plasma Polymerization of Ethylene

Abstract: Sodium nanoclay was modified by plasma polymerization using ethylene gas. Due to the complexity of its lamellar morphology that prevents ethylene from entering into the clay galleries, a new two‐step strategy was employed. This method proved to be effective in overcoming the limited accessibility by first exposing the nanoclay to ethylene under a pressure of 0.14 MPa (1.4 kg · cm−2), followed by the ethylene plasma polymerization while within the clay galleries. Fourier transform infrared (FTIR)spectroscopy, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…The spectrum of N116 shows a band at 3615 cm −1 due to the OH stretching coupled to an aluminum atom (Al–OH). The decreasing peak intensity at this wave number after air plasma treatment indicates the clay dehydration . The infrared spectrum of untreated N116 revealed a weak infrared band at 3385 cm −1 due to the –OH band stretch in Al–OH and Si–OH .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The spectrum of N116 shows a band at 3615 cm −1 due to the OH stretching coupled to an aluminum atom (Al–OH). The decreasing peak intensity at this wave number after air plasma treatment indicates the clay dehydration . The infrared spectrum of untreated N116 revealed a weak infrared band at 3385 cm −1 due to the –OH band stretch in Al–OH and Si–OH .…”
Section: Resultsmentioning
confidence: 96%
“…There are only several literature references on this topic in which the surface of clay particles is modified by plasma . Scaffaro et al found that polyamide 6 and poly[ethylene‐co‐(vinyl acetate)] nanocomposites showed a remarkable increase of the elastic modulus when radio‐frequency plasma and organically modified montmorillonite were used.…”
Section: Introductionmentioning
confidence: 99%
“…Glow discharge plasma is a well-known technique for the polymerization of various organic compounds, including naphthalene, ethylene, perfluorocarbons, acetonitrile, acrylonitrile, pyridine, ferrocene, 1,2-dicyanoethylene, and tetracyanoethylene3456. The polymerization of organic compounds using the glow discharge technique is however not fully understood due to the complex roles played by the organic compounds and their functional groups67.…”
mentioning
confidence: 99%
“…Figure 5, the FTIR spectra of pristine Na + -MMT and Na + -MMT/MMA are shown. In these spectra, the previously reported characteristic signals of nanoclay can be observed [36,46]. The signal at 3640 cm −1 is attributed to the Al-OH bond stretching, while the presence of absorbed humidity is observed at 3440 cm −1 .…”
Section: Characterization Of Nanoclaymentioning
confidence: 52%
“…It is a relatively simple, rapid, dry, and environment-friendly technique that is used to modify the surface of a great variety of materials. Even if this technique is normally used to modify the surface of different polymeric substrates, it has been used with success to modify different nanoparticles and other surfaces like zinc oxide, iron oxide, aluminum oxide, titanium oxide, carbon nanofibers (CNFs), CNTs, nanoclays [5,7,15,16,[31][32][33][34][35][36], and quartz [37,38]. Treatment with plasma can add a nanometric film that covers nanoparticles, modifying their surface properties.…”
Section: Introductionmentioning
confidence: 99%